Developing Materials for English Specific Purposes in Hospital Administration Department - Naajihah Mafruudloh (ELITE Association Indonesia, 2020)
In teaching English specific Purposes, the teachers should have proper materials. The materials should have relation with the students’ needed and field of study. To cover suitable materials, the teacher should design and make it properly to make the students well prepared for real life situations of the target language. This study aims to describe and presents a course outline to develop materials for ESP class that used by EFL teachers with an ESP students. This research focuses on ESP for Hospital Administration. The texts used are taken from authentic sources. Firstly, the researcher discussed the main problems teachers usually face when designing ESP material. Then, the researcher presents a course outline to develop the materials ESP for Hospital Administration. The texts used for the materials development are taken from authentic sources.